Glucose Oxidase Sensing: 3D Macroporous Zinc Compound/Silicone Hybrid Foams for Amperometric Sensing of Glucose Oxidase (Global Challenges 2/2019). Issue 2 (3rd February 2019) - Wu, Ye; Fu, Hao; Xie, Weiwei; Lin, Yingcheng; Kizilkaya, Orhan; Xu, Jian
Abstract : In article number1800049, Yingcheng Lin, Orhan Kizilkaya, Jian Xu, and co‐workers demonstrate a zinc compound/silicone hybrid foam that can be used for amperometric sensing of glucose oxidase. An increase in the concentration of the glucose oxidase led to an increase of detected current. This is explained with a possible mechanism for the formation of extra electron bands.